State Policy Towards Demographic Changes in Poland - Andruszkiewicz, Iwetta; Łebkowska, Joanna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
The aim of the article is to show that the modern civilization of technological, medical, structural and world-view progress determines the negative changes in the structure of families and the growth of the elderly population. Among the research hypotheses, in particular, it should be pointed out that the modern family policy should take into account the procreative context, as well as the family context with the participation of the older generation, as a consumer and participant in market services. The conclusions proposed by the authors concern a number of solutions in the field of social policy. The unfavorable demographic situation in the European Union raises specific challenges for social and demographic policy, among which, we should point out the changes in attitudes and individual behavior towards marriage and starting a family, changes in procreation attitudes, improving the quality of life of all generations, ensuring active participation of all generations in the demographic and socio-economic development of the country. The article has been written using the following research methods: descriptive, comparative and historical analysis.

Celem artykułu jest ukazanie, że współczesna cywilizacja postępu technologicznego, medycznego, strukturalnego i światopoglądowego determinuje negatywne zmiany w strukturze rodzin oraz wzrost populacji osób starszych. Wśród postawionych hipotez badawczych w szczególności wskazać należy na fakt, iż współczesna polityka rodzinna powinna uwzględniać kontekst prokreacyjny, jak i rodzinny z udziałem starszego pokolenia, jako konsumenta i uczestnika usług rynkowych. Wnioski, które proponują autorki dotykają szeregu rozwiązań w zakresie polityki społecznej. Niekorzystna sytuacja demograficzna w Unii Europejskiej wyłania określone wyzwania dla polityki społecznej i demograficznej, wśród których wskazać należy na zmiany w postawach i zachowaniach indywidualnych wobec kwestii zawierania małżeństw i zakładania rodziny, zmiany w postawach prokreacyjnych, podnoszenie jakości życia wszystkich pokoleń, zapewnienie aktywnego uczestnictwa wszystkim pokoleniom w rozwoju demograficznym i społeczno-ekonomicznym kraju. Artykuł powstał z wykorzystaniem następujących metod badawczych: opisowej, porównawczej i analizy historycznej.
Polityka państwa wobec przemian demograficznych w Polsce
Keywords: social policy; demographic policy; family; women labour force participation; economic and social development; polityka społeczna; polityka demograficzna; rodzina; aktywność zawodowa kobiet; rozwój ekonomiczno-społeczny